A phytochemical screening, antioxidant and antibacterial activity analysis in the leaves, stems and roots of Portulacaria afra - Domonique Courtney Basson; Thabiso Katlego Teffo; Ida Masana Risenga (Shahrekord University of Medical Sciences, 2023)
Introduction: Portulacaria afra is a medicinal plant commonly used among African traditional healers to treat skin conditions and dehydration. The aim of this study was to scientifically validate the use of P. afra among traditional healers. Methods: Standard phytochemical colour tests were used to determine the presence of ten phytochemicals, using four solvents of varying polarities (hexane, ethyl acetate, methanol, and water). The antioxidant activity was determined using 1-diphenyl-2-picrylhydrazyl (DPPH) and hydrogen peroxide scavenging assays. An agar-well diffusion assay was used to determine the antibacterial activities of the leaves, stems, and roots of P. afra against Staphylococcus aureus and Escherichia coli. Results: P. afra exhibited a high phytochemical presence in the methanolic extracts, with seven out of the 10 phytochemical groups present. Flavonoids and phlobatannins were absent in all of the plant's extracts. The methanolic root extract exhibited the highest DPPH scavenging activity (IC50=0.39) whilst the hexane leaf extract (IC50= 14.83) was the only extract to exceed the acceptable upper limit. The scavenging activity of the plant was stronger against hydrogen peroxide than it was against DPPH. The methanolic and hot water stem extracts displayed the largest zone of inhibition (of 20 mm) against E. coli. The cold-water and room-temperature water extracts, of all three plant parts, showed no zone of inhibition against either bacterial strain. Conclusion: P. afra has the capacity to be used as a nutritional supplement for its antioxidant properties, while the antibacterial properties may provide relief against E. coli infections.